Bulevirtide‐based treatment strategies for chronic hepatitis delta: A review - Degasperi, Elisabetta; Anolli, Maria Paola; Lampertico, Pietro (Journal of viral hepatitis, 2023)
Chronic hepatitis Delta (CHD) is a rare and severe form of chronic viral hepatitis. Until recently, the only therapeutic approach has been the off‐label use of a 48 weeks course of PegInterferon alpha (PegIFNα), that was characterized by suboptimal efficacy and burdened by significant side effects that limited treatment applicability in patients with advanced liver disease. In July 2020, European Medicines Agency (EMA) conditionally approved the entry inhibitor Bulevirtde (BLV) at the dose of 2 mg/day for the treatment of adult patients with compensated CHD. Efficacy and safety of BLV in CHD have been evaluated in clinical trials either as monotherapy or in combination with PegIFNα. These results were confirmed by real‐life studies, which also evaluated long‐term BLV monotherapy in patients with advanced compensated cirrhosis. Notwithstanding these promising results there are still several issues to be addressed, such as the optimal duration of the treatment, the rates of off‐therapy responses, as well as the long‐term clinical benefits. This review summarizes updated and current literature data about clinical trials and real‐life studies with BLV monotherapy and/or in combination with PegIFNα.